Plan de marketing estratègico para la horchata La Laureñita en la ciudad de Loja. - Espinoza Gálvez, Javier Arturo (2012)
This research work is intended to support the Craft Association of Medicinal Plants "The Laureñita" ASAPLAMELL of the parish of the country Lauro Guerrero we request to improve the quality of life of its partners and associates who in turn are the suppliers of raw materials for production and marketing. Our research proposal focuses on the management of the ASAPLAMELL make good decisions about production, marketing policies, good food and agricultural practices, marketing strategies and fair trade association. A first step involved in the research work was to conduct a situational analysis which includes a Diagnostic Procedure; it filled us how is going the Association and therefore the community enterprise. Subsequently, we investigated the mission, vision and objectives that are chasing the Association. Concomitantly with the above, we break down the management levels to proceed to develop the Organic-Functional Flowchart. Additionally, we analyze the product line currently has Horchata "La Laureñita" financial and technical resources. A second step was to conduct the external analysis of the ASAPLAMELL, in which competition auscultate, socioeconomic factors to have a clearer idea of who we are fighting with the current market. A third step was to perform market research in order to get into what will be the preamble to the Strategic Marketing Plan, because as you know your market research is to obtain a commercial X macro environment within the sector of plant medicinal. A fourth step in analyzing home to "The Laureñita" with a SWOT and subsequently measured with arrays MEFE, MEFI and will address that later. To strengthen the evaluation, we investigate the methods used with famed Diamond Porter, BCG Matrix, disintegration of competitive advantage, supporting the definition of the markets where we intend to attack with our research and proposal. A fifth step is the actual implementation of the marketing mix where its components will be worked independently but with a millimetric coordination to meet its objectives and implementing the strategies. A sixth step, we propose a budget broken down by each strategic line. Subsequently the development of the matrix control and monitoring of Strategic Marketing Plan. And finally, we completed with conclusions and recommendations. It is noteworthy that for each there will be a conclusion or conclusions depending on their scope and impact.